Perception of the impact of physical-sports programs for people with disabilities in the Ñuble Region, Chile - Reyes Rodríguez, Alixon David; Jorquera Becerra, Ignacio; Gálvez Contreras, Eimmy Noemí; Godoy Tapia, Cristian; Pavez-Adasme, Gustavo; Gómez-Álvarez, Nicolás; Olate-Pastén, Yesenia (SPORT TK-EuroAmerican Journal of Sport Sciences, 2024)
The aim of this research was to analyze the perception of people with disabilities regarding the impact on their health and quality of life of the physical-sports, and recreational activity programs in which they participate in the Ñuble region. The research used a qualitative approach, with a non-experimental, transectional design. The units of analysis were the beneficiaries of the programs, applying an intentional probabilistic sampling. In addition, the "snowball" technique was used to broaden the base of informants, and the in-depth interview technique was also used. In the interviews, the participants commented that through the physical-sports programs of the Ñuble region, they have achieved substantial improvements in terms of social insertion and relationships, feeling social recognition; they also report self-efficacy and the importance of carrying out activities without the help of another person, whether in daily tasks, transportation or educational commitments. In several cases, some beneficiaries have generated an impulse towards work, politics and national and international sports, however, the beneficiaries of the programs commented on the need to strengthen policies for the dissemination and access to these programs, as well as the importance of improving public policies and expanding the coverage levels of the programs.